(3GdeOhfI aj Gdabg GdeGdcis - (3CHh YHO Gddg YHO GdQMef Hf GdbGSe GdeGdcj,J (B191 (3g` s; (3QhGjI SMfhf Hf SYjO GdJfhMis ((3YHO Gddg Hf eMeO Hf YHO GdhGQK s)
(3ChdgG (B:s
(3jHOC HcJGH GdhVhA , GdJhbjJ ajg , Hbhdg (B: (3bdJ dYHO GdQMef Hf GdbGSe CQGjJ GdhVhA cGf eGdc jhbJ ajg hGMOI Ch EKfJjf Ch KdGKG s
(3BNQgG (B:s
(3jfJgi , HcJGH GdLQGM ef cJGH GdOjGJ Hbhdg (B: (3Je cJGH GdOjGJ HMeO Gddg hYhfg hHJeGeg JeJ LejY cJH GdeOhfI s
(3fSNI Ydi Qb ZRGds
(3YdjgG JMHjSs
(3hQO GdYfhGf GdCUdi ai (B:(3c X (B2/ 1644s
(3JHUQI GdYfhGf (B:s
(3QhGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdeGdcjs